2000
DOI: 10.4049/jimmunol.164.12.6230
|View full text |Cite
|
Sign up to set email alerts
|

Melphalan and Other Anticancer Modalities Up-Regulate B7-1 Gene Expression in Tumor Cells

Abstract: In this study, we show that administration of low-dose melphalan (l-PAM, l-phenylalanine mustard) to mice bearing a large MOPC-315 plasmacytoma led to a rapid up-regulation of B7-1 (CD80), but not B7-2 (CD86), expression on the surface of MOPC-315 tumor cells. This l-PAM-induced preferential up-regulation of B7-1 surface expression was due, at least in part, to a direct effect of l-PAM on the tumor cells, as in vitro exposure of MOPC-315 tumor cells to l-PAM led to the preferential up-regulation of B7-1 surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 43 publications
1
60
0
Order By: Relevance
“…Opposite expression patterns of these costimulatory molecules were observed following L-PAM therapy of MOPC-315 tumor bearers (15). Specifically, B7-1 was up-regulated at the tumor site within 24 h after L-PAM treatment (15), whereas B7-2 was up-regulated after 48 h (11), which is similar to the time of up-regulation of B7-2 expression on APC exposed to the other stimuli (12)(13)(14).…”
Section: Mechanism Of Melphalansupporting
confidence: 58%
See 3 more Smart Citations
“…Opposite expression patterns of these costimulatory molecules were observed following L-PAM therapy of MOPC-315 tumor bearers (15). Specifically, B7-1 was up-regulated at the tumor site within 24 h after L-PAM treatment (15), whereas B7-2 was up-regulated after 48 h (11), which is similar to the time of up-regulation of B7-2 expression on APC exposed to the other stimuli (12)(13)(14).…”
Section: Mechanism Of Melphalansupporting
confidence: 58%
“…Our studies revealed that within 24 h after in vitro exposure of MOPC-315 tumor cells to L-PAM, the tumor cells exhibited up-regulated B7-1 surface expression and unaltered B7-2 surface expression, which was high to start with (15). This effect of L-PAM was not restricted to MOPC-315 tumor cells, as preferential up-regulation of B7-1 surface expression was also observed within 24 h after in vitro exposure of P815 tumor cells to L-PAM (15). Subsequent studies into the mechanism through which L-PAM leads to up-regulation of B7-1 surface expression used P815 tumor cells because, unlike MOPC-315 tumor cells, P815 tumor cells do not constitutively express either the B7-1 or the B7-2 molecule on their surface (15).…”
Section: Mechanism Of Melphalanmentioning
confidence: 77%
See 2 more Smart Citations
“…B7-1 (CD80) is expressed in MOPC315 and P815 cells exposed to lowdose melphalan, as well as in splenic lymphocytes, and expression of these costimulatory molecules plays a crucial role in enhancing tumor immunity in these systems (63)(64)(65). Similarly, DAAs may confer upon L1210 lymphoma the ability to act as APCs for their own tumor-associated Ags via up-regulation of MHC class II and costimulatory molecules.…”
Section: Role Of Ciita In Daa-induced Increases In Immunogenicity Of mentioning
confidence: 99%